2008
DOI: 10.1517/17460441.3.5.475
|View full text |Cite
|
Sign up to set email alerts
|

Potential directions for drug development for osteoarthritis

Abstract: Background: Osteoarthritis (OA) is a frustrating disease for both patient and physician because neither cause nor cure is known and there are currently no disease-modifying drugs. Objective: To review current therapeutic approaches as well as new findings regarding OA pathoetiology that could form the basis of future direction for the development of drugs to prevent or slow down disease progression. Methods: After reviewing disease progression in human OA, as demonstrated by histological analyses, the reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 103 publications
(111 reference statements)
0
5
0
3
Order By: Relevance
“…Based on these findings, we assume that GlcN and BAY can modulate the gene expression patterns by altering DNA methylation status. Of course inflammatory cytokines including IL-1β, OSM and TNFα act not only via the NF-kB pathway but also through number of other signaling pathways (JNK, p38, and ERK), and complete suppression of cytokine/protease activity would require coordinated inhibition of more than one pathway [11,19,20]. Thus, although the current studies cannot advocate the use of BAY in OA, the observations indicate the importance and need to further dissect the mechanisms, efficacy and safety of NF-kB inhibition, and the epigenetic pathways involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, we assume that GlcN and BAY can modulate the gene expression patterns by altering DNA methylation status. Of course inflammatory cytokines including IL-1β, OSM and TNFα act not only via the NF-kB pathway but also through number of other signaling pathways (JNK, p38, and ERK), and complete suppression of cytokine/protease activity would require coordinated inhibition of more than one pathway [11,19,20]. Thus, although the current studies cannot advocate the use of BAY in OA, the observations indicate the importance and need to further dissect the mechanisms, efficacy and safety of NF-kB inhibition, and the epigenetic pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics, defined as the heritable modification in gene function without changes in the DNA sequence, including DNA methylation, histone modification and changes in chromatin structure, are important in the maintenance of the phenotype of the normal adult chondrocyte [7]. We and others have shown that chondrocytes in OA cartilage undergo a phenotypic change acquiring a gene expression repertoire characterized by the aberrant expression of a number of catabolic genes including IL1β [811]. In addition, DNA demethylation at specific CpG sites accounts for the aberrant expression of matrix metalloproteinases ( MMP ) 3, 9 and 13, ADAMTS4 and IL1β in human articular chondrocytes [1013].…”
Section: Introductionmentioning
confidence: 99%
“…RA sinoviyumunda NF-κB proteinleri p50 ve p65'in makrofajlarda, sinoviyal örtü hücrelerinde ve vasküler endotelde bol miktarda bulunduğu ve NF-κB'nin romatoid artrit için patolojik olabileceğini bildirmiştir (21). Diğer bir araştırmada NF-κB'nin OA'lı hasta kondrositlerinde, anormal gen ürünlerinin uyarılması ve normal kondrosit gen ürünleri üretiminin baskılanmasında etkili olduğu ileri sürülmüştür (12). NF-κB, inflamatuar sitokinlerle birlikte çeşitli hücre dışı matriks yıkım proteinlerinin ekspresyonlarını artırdığı gösterilmiştir (12).…”
Section: Discussionunclassified
“…Diğer bir araştırmada NF-κB'nin OA'lı hasta kondrositlerinde, anormal gen ürünlerinin uyarılması ve normal kondrosit gen ürünleri üretiminin baskılanmasında etkili olduğu ileri sürülmüştür (12). NF-κB, inflamatuar sitokinlerle birlikte çeşitli hücre dışı matriks yıkım proteinlerinin ekspresyonlarını artırdığı gösterilmiştir (12). OA ve RA hastalarından elde edilen fibroblast-benzeri sinoviyosit (FLS) hücrelerde NF-κB'nın aktifleşmesinde görevli IκB (IKK)'nin varlığı gösterilmiştir (22).…”
Section: Discussionunclassified
See 1 more Smart Citation